Enhanced drought tolerance and photosynthetic efficiency in Arabidopsis by overexpressing phosphoenolpyruvate carboxylase from a single-cell C4 halophyte Suaeda aralocaspica - Li, Caixia; Wang, Juan; Lan, Haiyan; Yu, Qinghui (Frontiers in Plant Science, 2024)
In crop genetic improvement, the introduction of C4 plants' characteristics, known for high photosynthetic efficiency and water utilization, into C3 plants has been a significant challenge. This study investigates the effects of the desert halophyte Suaeda aralocaspica SaPEPC1 gene from a single-cell C4 photosythetic pathway, on drought resistance and photosynthetic performance in Arabidopsis. We used transgenic Arabidopsis with Zea mays ZmPEPC1 from C4 plant with classic Kranz anatomical structure and Arabidopsis AtPEPC1 from C3 photosynthetic cycle plants as controls. The results demonstrated that C4 photosynthetic-type PEPCs could improve drought resistance in plants through stomatal closure, promoting antioxidant enzyme accumulation, and reducing reactive oxygen species (ROS) accumulation. Overexpression of SaPEPC1 was significantly more effective than ZmPEPC1 in enhancing drought tolerance. Notably, overexpressed SaPEPC1 significantly improved light saturation intensity, electron transport rate (ETR), photosynthetic rate, and photoprotection ability under intense light. Furthermore, overexpression SaPEPC1 or ZmPEPC1 enhanced the activity of key C4 photosynthetic enzymes, including phosphoenolpyruvate carboxylase (PEPC), pyruvate orthophosphate dikinase (PPDK) and NADP-malic enzyme (NADP-ME), and promoted photosynthetic product sugar accumulation. However, with AtPEPC1 overexpression showing no obvious improvement effect on drought and photosynthetic performance.Therefore, these results indicated that introducing C4-type PEPC into C3 plants can significantly enhance drought resistance and photosynthetic performance. However, SaPEPC1 from a single-cell C4 cycle plant exhibits more significant effect in ETR and PSII photosynthesis performance than ZmPEPC1 from a classical C4 anatomical structure plant, although the underlying mechanism requires further exploration.